CONFIRMATORY ANALYSIS AS A TOOL FOR FORMING INDICATORS OF SELF-EFFICACY, FINANCIAL BEHAVIOR, AND FINANCIAL WELL-BEING - Ratnawati, Ratnawati; Ningsih, Ayu Agus Tya (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
Small and Medium Industries are a form of small business that operates in several fields that can become the foundation of the country's economy. The creative industry makes many contributions by providing employment opportunities, increasing state income, and alleviating poverty. Finance plays a crucial role in demonstrating the ability of small and medium sized business owners to manage their operations by enlisting the help of labor, involving third parties, and turning a profit. The importance of financial self-confidence in achieving financial prosperity is very important. It plays a role in ensuring that SMEs can manage and decide on all forms of financial roles that they carry out, supported by good financial behavior. This research aims to analyze confirmatory factors of self-efficacy and financial behavior to improve financial well-being. Data analysis used in the research used confirmatory factor analysis (CFA) techniques with Structural Equation Modeling (SEM) software. The results of confirmatory factor analysis reveal that the strongest indicator that contributes to financial well-being is financial management skills, for the financial self-efficacy variable the indicator that has the highest contribution is financial decision making and the credit management indicator contributes the most to the financial behavior variable.